Pengaruh adversity quotient terhadap kemandirian, motivasi, dan hasil belajar siswa - Hakim Setyobudi; Syamsuri Syamsuri; Maman Fathurrohman (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2023)
The learning process at school will get results that are in accordance with educational goals, including being influenced by Adversity Quotient (AQ) or the intelligence of overcoming difficulties and obstacles in the learning process. AQ is one of the elements that can affect independence, motivation and learning outcomes in mathematics.This type of research is a survey research with a quantitative approach to determine the structural equation model related to the Adversity Quotient variable on the independence, motivation, and mathematics learning outcomes of high school students. This research was carried out in five public high schools in semester 2 of the 2021-2022 academic year. . To obtain complete and accurate data in this study, the data collection technique carried out by the researcher is the questionnaire method (questionnaire).The results of the study revealed that the structural equation model obtained had a coefficient of determination of 88.5%, meaning that the influence of the adversity quotient on independence, motivation, and mathematics learning outcomes was 88.50%, while the remaining 11.5% was explained by other factors. In addition, there is a positive and significant influence on learning independence with a contribution of 94.1% means that it has a positive and significant influence on independent learning. The influence of the adversity quotient on learning motivation is 94.3%, meaning that it has a positive and significant influence on learning motivation. And obtained a positive and significant influence between the adversity quotient on learning outcomes 31.4%, meaning that it has a positive and significant contribution to learning outcomes.